2021
DOI: 10.1021/acs.inorgchem.1c01011
|View full text |Cite
|
Sign up to set email alerts
|

Polar Structure and Two-Dimensional Heisenberg Antiferromagnetic Properties of Arylamine-Based Manganese Chloride Layered Organic–Inorganic Perovskites

Abstract: The breaking of inversion symmetry can enhance the multifunctional properties of layered hybrid organic–inorganic perovskites. However, the mechanisms by which inversion symmetry can be broken are not well-understood. Here, we study a series of MnCl 4 -based 2D perovskites with arylamine cations, namely, (C 6 H 5 C x H 2 x NH 3 ) 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 56 publications
1
35
0
Order By: Relevance
“…More significantly, meta- F-substitution in (3-FbaH) 2 CuCl 4 leads to a polar material, with the symmetry being broken by subtle displacements in the positions of the 3-FbaH moieties, with resulting advantages in H-bonding opportunities to the [CuCl 4 ] ∞ layers. This symmetry-breaking mechanism seems related to, but distinct from, that recently seen in some manganese chloride layered perovskites 46 where the rotational degree of freedom of extra-cyclic chains is suggested to be responsible. In addition, in this case, we see that the F-substitution of the phenyl ring also plays a key role.…”
Section: Discussionsupporting
confidence: 54%
“…More significantly, meta- F-substitution in (3-FbaH) 2 CuCl 4 leads to a polar material, with the symmetry being broken by subtle displacements in the positions of the 3-FbaH moieties, with resulting advantages in H-bonding opportunities to the [CuCl 4 ] ∞ layers. This symmetry-breaking mechanism seems related to, but distinct from, that recently seen in some manganese chloride layered perovskites 46 where the rotational degree of freedom of extra-cyclic chains is suggested to be responsible. In addition, in this case, we see that the F-substitution of the phenyl ring also plays a key role.…”
Section: Discussionsupporting
confidence: 54%
“…In the solid state, these structures consist of an alternation of anionic metal halide layers partitioned by arrays of cations. The inorganic regions of the copper, 39 nickel, 40 and manganese 41,42 compounds consist of distorted MCl 6 octahedra featuring MCl 4 layers of square planar metal centres sharing bridging chloro ligands, and two apical terminal Cl ligands on each metal centre. 43 At variance with those, reported tetrahedral [CoCl 4 ] 2− groups were found in the cobaltate salts.…”
Section: Resultsmentioning
confidence: 99%
“…Another study by Septiany et al 12 discussed the effects of methylene group on magnetic properties in manganese-based 2D perovskites. They found that the bond angles in PPA-Mn had indeed shifted from 180°, compared to PEA-Mn.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, changes in the dimensional structure of the perovskites could bring major alterations to the material properties. In three-dimensional materials, any disparities present within the materials are uniform in all three geometrical axes; therefore, no noticeable changes would be observed via highly sensitive angular-dependent probing such as X-ray absorption spectroscopy (XAS). On the other hand, materials belonging to low-dimensional structures are organized in different arrangements with their distinct behavior. Two-dimensional materials are constructed of entities arranged within the same plane, leading to the materials exhibiting a unique angular-dependent response upon probing by X-ray irradiation. This combination of highly sensitive spectroscopy and the peculiar behavior of 2D materials could provide more insight into the structural phase transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation